Charismatic and Pentecostal Social Orientations in Nigeria - Gaiya, Musa A. B. (Nova religio, 2015)
This article identifies two responses to social challenge by charismatic Pentecostal churches in Nigeria. I argue that churches taking a centripetal position are either socially passive or they collude with corrupt leaders and groups who undermine efforts toward political, social and human improvement; yet, in their engagement with society they offer spiritual solutions to myriad social and political problems. Conversely, churches taking a centrifugal approach try to confront political and social problems, but these churches are relatively few and located primarily in Lagos, although they are growing in influence. I conclude that charismatic Pentecostalism in Nigeria currently is shifting from strictly spiritual solutions to sociopolitical problems to an emphasis on meeting social needs in practical ways.